2016
DOI: 10.3126/dsaj.v10i0.15879
|View full text |Cite
|
Sign up to set email alerts
|

Remittance Received by Households of Western Chitwan Valley, Nepal: Does Migrant’s Destination Make a Difference?

Abstract: Studies on migration in Nepal primarily focused on the causes of migration, in general. While a few studies examined the remittances received or sent by migrants, there is little information about the variation in remittances received by households by migrant's destination. Thus, this exploratory study attempts to answer: Does the extent to which households receive remittances vary by migrant's destination? Using the data collected in 2013 from the western Chitwan Valley of Nepal, the findings from multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The variation in the inflows of remittance has increased inequality in society, and inflows have varied due to types, levels, and destinations of migrants (Bhandari 2016). The variation on the inflows is creating a complex to use such remittance on poverty alleviation and human capital development.…”
Section: Influences Of Covid-19 On National Economymentioning
confidence: 99%
“…The variation in the inflows of remittance has increased inequality in society, and inflows have varied due to types, levels, and destinations of migrants (Bhandari 2016). The variation on the inflows is creating a complex to use such remittance on poverty alleviation and human capital development.…”
Section: Influences Of Covid-19 On National Economymentioning
confidence: 99%
“…The Nepal Migration Survey 2009 estimates that 41 percent of Nepali international migrants were in India, 38 percent in the Persian Gulf countries, 12 percent in Malaysia, and 9 percent in other countries, largely dominated by South Korea, Japan, North America, the United Kingdom, and Australia (World Bank 2011). Despite rather large changes in destinations, much of this migration is still short-term, labor-oriented, and undertaken by individuals who remit money to their families remaining in Nepal (Bhandari 2016). Migration of whole households is less common, and family reunification is not possible on employment visas to the Persian Gulf and several Asian countries (Bhandari 2016; Ghimire et al 2017).…”
Section: Settingmentioning
confidence: 99%
“…Despite rather large changes in destinations, much of this migration is still short-term, labor-oriented, and undertaken by individuals who remit money to their families remaining in Nepal (Bhandari 2016). Migration of whole households is less common, and family reunification is not possible on employment visas to the Persian Gulf and several Asian countries (Bhandari 2016; Ghimire et al 2017).…”
Section: Settingmentioning
confidence: 99%
“…Remittances from international migrants are very important elements of the Nepali economy; they accounted for roughly 29 % of Nepali GDP in 2014, with Nepal ranking the world's third largest in terms of remittance receipts per capita (World Bank 2016). Also, remittances in 2014/2015 were the third (17.6 %) most important source of a household's income after salary, wages, allowances, and pensions (30.3%) and business income (24.4%) (Nepal Rastra Bank 2016; see also Adhikari 2001;Bhandari 2016;Seddon et al 2002). Bhandari and Chaudhary (2017) reported that remittance-receiving households use remittances for a wide variety of productive and consumptive purposes.…”
Section: Study Settingmentioning
confidence: 99%